2021
DOI: 10.1038/s41598-021-91409-7
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine inhibits ROS generation in response to glycoprotein VI stimulation

Abstract: Colchicine inhibits coronary and cerebrovascular events in patients with coronary artery disease (CAD), and although known to have anti-inflammatory properties, its mechanisms of action are incompletely understood. In this study, we investigated the effects of colchicine on platelet activation with a particular focus on its effects on activation via the collagen glycoprotein (GP)VI receptor, P2Y12 receptor, and procoagulant platelet formation. Therapeutic concentrations of colchicine in vitro (equivalent to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…In CVD therapy, β-TG and mean platelet volume are lower in patients treated with colchicine [ 107 , 111 ]. Pennings et al [ 112 ] studied the impact of colchicine on platelet activation. They found that pharmacologically relevant concentrations of colchicine (20 nmol/L) in vivo significantly inhibited platelet aggregation through the collagen glycoprotein receptor and P2Y12 receptors.…”
Section: Mechanism Of Action Of Colchicine In Cardiovascular Disease Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CVD therapy, β-TG and mean platelet volume are lower in patients treated with colchicine [ 107 , 111 ]. Pennings et al [ 112 ] studied the impact of colchicine on platelet activation. They found that pharmacologically relevant concentrations of colchicine (20 nmol/L) in vivo significantly inhibited platelet aggregation through the collagen glycoprotein receptor and P2Y12 receptors.…”
Section: Mechanism Of Action Of Colchicine In Cardiovascular Disease Preventionmentioning
confidence: 99%
“…Colchicine disturbs microtubule dynamics through binding to tubulin and then inhibits the process of cleavage of pro-IL-18 and pro-IL-1β into IL-18 and IL-1β, respectively. Colchicine reduces ROS formation [ 58 , 112 ], as well as NO and IL-1β release in mouse macrophages [ 58 ]. Colchicine suppresses pore formation, such as P2X7 and P2X2, to inhibit ATP-induced NLRP3 inflammasome activation [ 140 ] (Fig.…”
Section: Molecular and Biochemical Targets Of Colchicinementioning
confidence: 99%
“…Future studies in the setting of coronary artery disease have demonstrated an additional anti-aggregatory action when platelet activation was induced by agonists [ 172 , 173 ]. A recent study by Pennings et al revealed the modulation of GPVI receptor pathway as the antiplatelet mechanism of action of colchicine [ 174 ]. It could be those additional antiplatelet effects that mediate the protective effect of colchicine in atherosclerotic diseases as evidenced in large randomized clinical trials [ 175 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Interestingly, when tocilizumab was administered to COVID-19 patients, an early and sustained increase in platelet count was observed, possibly signifying reduced platelet consumption and less thrombosis [160,161]. Finally, colchicine has undoubtedly received the most scientific attention in this aspect, with several studies highlighting its potential as an adjunctive antiplatelet approach [159,[162][163][164], which might be responsible for the beneficial effects observed in patients with a recent acute coronary syndrome or chronic coronary syndromes [80,152]. Despite being studied in the setting of COVID-19, the effect of antiinflammatory agents on established platelet activation parameters has not been assessed in this patient population and can only be speculated on.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%